Medicinal Plants used for the Traditional Management of Skin Disorders in Doodpathri area of Budgam, Jammu and Kashmir - Mir, Tawseef Ahmad; Khare, Rakesh Kumar; Jan, Muatasim (Indian Forester, 2022)
Skin diseases are a major health concern in present world. These diseases effect all the individuals irrespective of age and gender. The aim of the present study was to document the ethnomedicinal information of plants used to treat various skin disorders in Doodpathri area of district Budgam of Jammu and Kashmir. This is the first ever ethnomedicinal study of therapeutic herbs utilized by the indigenous people in the present study area for the treatment of skin disorders. In this study a total of 36 medicinal plants belonging to 34 genera and 25 families were recorded to be used for skin disorders by the indigenous people. Asteraceae was found to be the dominant family with a species contribution of nine species. It was found that there is a very little information available about cultivation, sustainable harvesting and uses of these medicinal plant species. There is a dire need to create awareness among the local and government communities for the preservation of medicinal flora of the area.